Guidelines of the International Headache Society for clinical trials with neuromodulation devices for the treatment of migraine. (October 2021) - Tassorelli, Cristina; Diener, Hans-Christoph; Silberstein, Stephen D; Dodick, David W; Goadsby, Peter J; Jensen, Rigmor H; Magis, Delphine; Pozo-Rosich, Patricia; Yuan, Hsiangkuo; Martinelli, Daniele; Hoek, Thomas van den; Deen, Marie; et al.
Background: Although the European Medicines Agency and the US Food and Drug Administration have cleared several devices that use neuromodulation to provide clinical benefits in the acute or preventive treatment of migraine, the Clinical Trials Committee of the International Headache Society has not developed guidelines specifically for clinical trials of neuromodulation devices. In recognition of the distinct needs and challenges associated with their assessment in controlled trials, the Committee provides these recommendations for optimizing the design and conduct of controlled trials of neuromodulation devices for the acute and/or preventive treatment of migraine. Methods: An international group of headache scientists and clinicians with expertise in neuromodulation evaluated clinical trials involving neuromodulation devices that have been published since 2000. The Clinical Trials Committee incorporated findings from this expert analysis into a new guideline for clinical trials of neuromodulation devices for the treatment of migraine. Results: Key terms were defined and recommendations provided relative to the assessment of neuromodulation devices for acute treatment in adults, preventive treatment in adults, and acute and preventive treatment in children and adolescents. Ethical and administrative responsibilities were outlined, and a bibliography of previous research involving neuromodulation devices was created. Conclusions: Adoption of these recommendations will improve the quality of evidence regarding this important area in migraine treatment.